2020
DOI: 10.1093/femsre/fuaa047
|View full text |Cite
|
Sign up to set email alerts
|

Eco-evolutionary feedbacks mediated by bacterial membrane vesicles

Abstract: Bacterial membrane vesicles (BMVs) are spherical extracellular organelles whose cargo is enclosed by a biological membrane. The cargo can be delivered to distant parts of a given habitat in a protected and concentrated manner. This review presents current knowledge about BMVs in the context of bacterial eco-evolutionary dynamics among different environments and hosts. BMVs may play an important role in establishing and stabilizing bacterial communities in such environments; for example, bacterial populations m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 320 publications
0
12
0
Order By: Relevance
“…Interestingly, the periplasm is not necessarily the final localization of MBLs, since some of them can be packed into outer membrane vesicles (OMVs). All Gram-negative bacteria produce OMVs in response to a wide variety of environments (92)(93)(94)(95)(96). Bacterial OMVs, possessing a diameter of 20 to 250 nm, are spherical portions of the outer membrane that protrude and detach from growing cells.…”
Section: Mbls Beyond the Bacterial Cell: Protein Sorting Into Vesiclesmentioning
confidence: 99%
“…Interestingly, the periplasm is not necessarily the final localization of MBLs, since some of them can be packed into outer membrane vesicles (OMVs). All Gram-negative bacteria produce OMVs in response to a wide variety of environments (92)(93)(94)(95)(96). Bacterial OMVs, possessing a diameter of 20 to 250 nm, are spherical portions of the outer membrane that protrude and detach from growing cells.…”
Section: Mbls Beyond the Bacterial Cell: Protein Sorting Into Vesiclesmentioning
confidence: 99%
“…Innate immune cells can recognize conserved bacterial molecular structures known as pathogen-associated molecular patterns (PAMPs) through pattern-recognition receptors (PRRs), which are crucial for the development of appropriate immune responses (1,2). Even though the access of microbes to the immune cells is restricted physically in most situations, recent evidence have shown that the microbiota can communicate with the host through various effector molecules (3), such as short-chain fatty acids (SCFAs), lipopolysaccharide (LPS), proteins, and bacterial extracellular vesicles (BEVs) (4). Among these microbiota-secreted factors, BEV is likely to have a more important role in interkingdom interactions (5)(6)(7) for the release of vesicle-like structures is a universally conserved cellular process that occurs in all domains of life (8).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane vesicles (MVs) are spherical particles of 20-250 nm diameter on average and consist of a hydrosol enclosed by one or two biological membranes [13]. They can be divided into outer membrane vesicles (OMVs) and outer-inner membrane vesicles (O-IMVs), depending on their formation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of OMVs and O-IMVs formation has yet not been fully understood. It is suggested that MVs form as a consequence of an imbalance between membrane tension and osmotic pressure that leads to an extracellular protrusion of the membrane areas where peptidoglycan is detached [13]. The imbalance may be due to a disrupted lipid asymmetry [21].…”
Section: Introductionmentioning
confidence: 99%